Avicenna's Theory of Science Logic, Metaphysics, Epistemology - Strobino, Riccardo (Berkeley series in postclassical Islamic scholarship, 2021)
Avicenna is the most influential figure in the intellectual history of the Islamic world. This book is the first comprehensive study of his theory of science, which profoundly shaped his philosophical method and indirectly influenced philosophers and theologians not only in the Islamic world but also throughout Christian Europe and the medieval Jewish tradition. A sophisticated interpreter of Aristotle's Posterior Analytics, Avicenna took on the ambitious task of reorganizing Aristotelian philosophy of science into an applicable model of scientific reasoning, striving to identify conditions o.